Answer:
-7pi √3
Step-by-step explanation:
Treating pi as a variable, the simplified value can be written as;
-7pi √3
This can be obtained from using the following simple methodology;
pi(√3 -8 √3)
= pi (-7 √3)
Answer:
exponential
constant multiplicative rate of change
Step-by-step explanation:
Step-by-step explanation:
(a-b)^2=a^2-2ab+b^2
X^2-2(X)(5)+5^2
Ans C
X^2-10X+25
<span>idk why they want the dratted "k" . it is so simple w/o it !
in the form y = ab^x, a = 4000, b = 4400/4000 = 1.1, x = t/2
N = 4000*1.1^(13/2) = 7432 <------
-----------------
now you won't be satisfied with simplicity, so
4400 = 4000e^2k
e^2k = 1.1
k = ln 1.1/2 = .0477 to 4 dp
N(13) = 4000e^(13*.0477) = 7436 <------
note that apart from a roundabout way, you get a less accurate ans !</span>